2016
DOI: 10.1007/s10461-016-1552-1
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction Medication Prescription and Condomless Intercourse in HIV-Infected Men Who have Sex with Men in the United States

Abstract: Using nationally representative data, we assessed the prevalence of erectile dysfunction medication (EDM) prescription, and its association with insertive condomless anal intercourse (CAI) with an HIV-serodiscordant partner among sexually-active HIV-infected men who have sex with men (MSM) receiving medical care in the United States. Overall, 14% (95% CI 12–16) were prescribed EDM and 21% (95% CI 19–23) engaged in serodiscordant CAI. MSM who were prescribed EDM were more likely to engage in insertive CAI with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
0
7
0
6
Order By: Relevance
“…[36,37] This study does not confirm findings from 2005 and 2016 showing that HIV-infected MSM are more likely to engage in unprotected sex after EDM prescription. [11,13] This deviation from the literature may be due to a benefit of EDM prescription within a community care clinic that focuses on HIV treatment and prevention. This study did not measure the use of prescribed EDM in a "party" context.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…[36,37] This study does not confirm findings from 2005 and 2016 showing that HIV-infected MSM are more likely to engage in unprotected sex after EDM prescription. [11,13] This deviation from the literature may be due to a benefit of EDM prescription within a community care clinic that focuses on HIV treatment and prevention. This study did not measure the use of prescribed EDM in a "party" context.…”
Section: Discussionmentioning
confidence: 97%
“…This ran counter to our study hypothesis and similar studies in high-risk populations. [7,11,13,31,32] In terms of STI screening rates, scant literature exists on the impact of EDM prescription on STI screening practices. One VA-based study documented minimal STI testing in the period after EDM prescription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using individual-level data identified substances associated with specific anal sex behavior, e.g. erectile dysfunction drugs (EDD) and crystal methamphetamine with insertive anal sex (Mansergh et al, 2006;Lin, Mattson, Freedman, & Skarbinski, 2017) and poppers (amyl nitrites) with receptive anal sex (Drumright, Gorbach, Little, & Strathdee, 2009). However, event-level analyses on substance use and ELV remain rare (Rich et al, 2016), even though the majority of GBM self-identify as versatile (Hart et al, 2003).…”
Section: Introductionmentioning
confidence: 99%